(untitled) (Colombia Medica, 1994)
This study was designed to identify what influences social and family support had on the emotional, adaptive process of women undergoing mastectomy for breast cancer. The global prevalence of «emotional morbidity» among study patients was 46.9%. It was measured in a period of 0-18 months without significant changes through time (p= 0.54). A self-questionnaire report (SQR) was used to determine emotional morbidity. A significant association statistically was found between emotional morbidity and family dysfunction (p = 0.008). The Family APGAR Index measured family dysfunction. Patients with family dysfunction were at higher risk than patients without family dysfunction for emotional disturbance (OR = 8 IC 1.45 - 57.9). Seventy-eight percent of patients had trouble adapting to jobs (p = 0.03), and 23% experienced marital problems (p = 0.002). These results demonstrate the importance of psychosocial aspects of medical care, including family and social support. Furthermore, they suggest a comprehensive rehabilitation program for this population.